Antifungal activity of endophytic microorganisms isolated from Acmella ciliata - Ortiz Ojeda, Cinthya Paola (2020)
The study of microorganisms that inhabit the interior of plants (endophytes) has acquired great importance because of their potential to produce bioactive metabolites. Acmella ciliata (known in Brazil as jambu) is a native herb of South America, used in regional gastronomy and folk medicine in Amazonas - Brazil, has antibacterial properties, and may be a useful host for bioactive endophytes. We isolated endophytic microorganisms from A. ciliata and evaluated their ability to inhibit pathogenic fungi. We isolated 56 fungi and 39 endophytic bacteria, most of them from the leaves. The endophyte isolates were then tested in antagonism assays against the phytopathogens Fusarium decemcellulare and Colletotrichum gloeosporioides. The best antagonism index values against C. gloeosporioides were obtained with the endophytic fungus UEA-253 (40%), and the endophytic bacterium UEA-135 (46.3%). The highest antagonism index values were obtained against F. decemcellulare with the fungus UEA-234 (47.2%), and the bacterium UEA-135 (44.8%). The endophytic fungi with inhibitory bioactivity belong to the genera Curvularia, Colletotrichum, Plectosphaerella and Sordariomycetes, while the endophytic bacteria belong to the genera Bacillus, Pseudomonas and Enterobacter. We conclude that the endophytic fungi and bacteria isolated from A. ciliata have potential for use in the biocontrol of F. decemcellulare and C. gloeosporioides.